The Impact of an Extreme Storm Event on the Barrier Beach of the Lefkada Lagoon, NE Ionian Sea (Greece) - GHIONIS, G.; POULOS, S. E.; VERYKIOU, E.; KARDITSA, A.; ALEXANDRAKIS, G.; ANDRIS, P. (Mediterranean Marine Science, 2015)
The present investigation examines the characteristics of a high energy storm event, that took place on November 9-11, 2007 in the NE Ionian Sea (eastern Mediterranean), and its impact upon the barrier beach that separates the Lefkada lagoon from the open Ionian Sea. The storm event was caused by NW winds with speeds exceeding 20 m/s (40 knots), which have an annual frequency of occurrence less than 0.015%. This high energy event produced waves with >5 m significant offshore height and 9.5 s period; these waves developed on 10th November during the rapid rise of barometric pressure (~1.4 hPa/hr), which followed the barometric pressure drop from 1020.5 hPa at 06:00 (UTC) of 9th November to 1001.7 hPa at 06:00 h (UTC) of 10th November. Secondary breaking at the shoreline produced wave heights >1.5 m, associated with a surge of >0.4 m and a run-up capability of >2.4 m. The waves managed to overtop the barrier beach (elevations ~2.5 m), lowering the seaward side of the barrier beach by 10-30 cm and causing a coastline retreat of 0.9 to 2.2 m; these morphological changes correspond volumetrically to a sediment loss of approximately 8 m3/m of coastline length from the sub-aerial part of the beach. During the last three decades a significant change in the frequency of occurrence and direction (from S-SW-W to N-NW-NE) of severe storms with wind speeds exceeding 40 knots has been recorded, affecting the sediment transport pattern and contributing to the erosion of the north beaches of Lefkada.